The 1B vaccine strain of Chlamydia abortus produces placental pathology indistinguishable from a wild type infection - Caspe, Sergio Gaston; Livingstone, Morag; Frew, David; Aitchison, Kevin; Wattegedera, Sean Ranjan; Entrican, Gary; Palarea-Albaladejo, Javier; McNeilly, Tom Nathan; Milne, Elspeth; Sargison, Neil Donald; Chianini, Francesca; Longbottom, David (Plos One, 2021)
Chlamydia abortus is one of the most commonly diagnosed causes of infectious abortion in small ruminants worldwide. Control of the disease (Enzootic Abortion of Ewes or EAE) is achieved using the commercial live, attenuated C. abortus 1B vaccine strain, which can be distinguished from virulent wild-type (wt) strains by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis. Published studies applying this typing method and whole-genome sequence analyses to cases of EAE in vaccinated and non-vaccinated animals have provided strong evidence that the 1B strain is not attenuated and can infect the placenta causing disease in some ewes. Therefore, the objective of this study was to characterise the lesions found in the placentas of ewes vaccinated with the 1B strain and to compare these to those resulting from a wt infection. A C. abortus-free flock of multiparous adult ewes was vaccinated twice, over three breeding seasons, each before mating, with the commercial C. abortus 1B vaccine strain (Cevac® Chlamydia, Ceva Animal Health Ltd.). In the second lambing season following vaccination, placentas (n = 117) were collected at parturition and analysed by C. abortus-specific real-time quantitative PCR (qPCR). Two placentas, from a single ewe, which gave birth to live twin lambs, were found to be positive by qPCR and viable organisms were recovered and identified as vaccine type (vt) by PCR-RFLP, with no evidence of any wt strain being present. All cotyledons from the vt-infected placentas were analysed by histopathology and immunohistochemistry and compared to those from wt-infected placentas. Both vt-infected placentas showed lesions typical of those found in a wt infection in terms of their severity, distribution, and associated intensity of antigen labelling. These results conclusively demonstrate that the 1B strain can infect the placenta, producing typical EAE placental lesions that are indistinguishable from those found in wt infected animals.